Legal Review of The Validity of Electronic Signatures in Authentic Deed - Muliani Zabir, Andi Sri; Darmadi, Nanang Sri; Kusriyah, Sri (TABELLIUS: Journal of Law, 2026)
The regulation of electronic signatures has been widely incorporated into various Indonesian laws and is used by many government agencies and the private sector. Notary practice under Law Number 2 of 2014 on the Notary function has been regulated with respect to the concept of cyber notary. However, it did not further specify or detail the use of an electronic signature in a notarial authentic deed. The purpose of this research is to analyze the existence and validity of electronic signatures in notarial authentic deeds and in other forms of notarial deeds that use electronic signatures. The method used is normative legal research with a law-regulation approach. The source and type of data used are secondary data from a literature review; the analysis is prescriptive. The results show that: 1) notaries in several countries, such as the United States and Japan, have been using electronic signatures in notarial authentic deeds, even making them in digital form, due to the legal foundation that ensures the notary can legally use the electronic signature in those countries. In Indonesia, an electronic signature has been used in government agencies, such as the Ministry of Agrarian Affairs and Spatial Planning and the Ministry of Law, as well as in private parties, such as the company that held a General Meeting of Shareholders of a Limited Liability Company via electronic means. 2) Signing of the original deed using an electronic signature could not be used in Indonesia since there is no clear legal foundation that regulates the notary's authority to use the electronic signature itself. If the notary continues to use the electronic signature on notarial authentic deeds, the deeds will be considered illegal and not authentic. At the same time, the use of an electronic signature on a copy of a notary deed is supposed to be possible as long as the original deed has been completely signed by every party, witness, and the notary, based on the Notary Position Regulations. The suggestion would be: 1) the government needs to implement a change in Law Number 2 of 2014 to accommodate the changing of the era. 2) The synergy between the government and notary organization would give legal certainty toward the use of an electronic signature on notarial authentic deeds by forming a legal foundation for using an electronic signature on the original deed, as well as the system and application that could make the use of an electronic signature on the practice of notary's duties easier.